OP0277-PC Persistence with Antiosteoporotic Drugs: A Retrospective Population-Based Cohort Study. (23rd January 2014) - Iolascon, G.; Capaldo, A.; Orlando, V.; Menditto, E.
Abstract : Background: Medication adherence, a synonym for compliance, is the extent to which patients take medication at the prescribed interval and dose. Persistence is defined as the period between the start and the interruption of a pharmacological treatment [1 ]. Numerous studies have demonstrated that, for a wide variety of diseases, and especially for chronic-degenerative diseases, inadequate persistence to prescribed therapies involving an increase in both the morbidity and mortality. Osteoporosis is one of the chronic medical conditions that require prolonged treatment. In osteoporotic patients, persistence to therapy is poor, resulting in reduced benefits (2 ), and increased risk of fracture(3 ). Recently, particular interest has been face to the use of administrative databases as a tool for indirect measurement of the levels of persistence(4 ). Objectives: The aim of this study is to analyze persistence with drug therapy in osteoporotic patients in the Campania region. Methods: We conducted a retrospective population-based cohort study to examine prescription data of 30, 348 subjects, males and females, aged ≥ 40 years, in Campania Region(Southern Italy). They received at least one prescription for osteoporosis medication in the period between January 1, 2009 and December 31, 2009. Subjects had not received osteoporosis medication in the year prior to the start of the study. They were followed for one year from the first prescription of an antiosteoporotic drug and persistence was assessed with the method of medication gaps. In addition, a survival analysis was performed by the Kaplan-Meier method and univariate sensitivity analysis. Results: The mean age of our samples was 69.1 years. 54.8% of subjects were persistent at 3 months, 32.8% at 6 months, 21.9% at 9 months and 15.9% at 12 months. The results of analysis of persistence for each drug are shown in Table 1 . Conclusions: Our study showed that in Southern Italy less than 30% of patients treated with antiosteoporotic drugs is persistent with therapy at one year and less than 40% at six months. Therefore most people using anti-osteoporotic drugs don't make any therapeutic benefit in order to reduce risk fracture. References: Cramer JA, Roy A, Burrell A, Fairchild CJ, Fuldeore MJ, Ollendorf DA, et al. Medication compliance and persistence: terminology and definitions. Value Health 2008;11:44–7. Sally W. Wade et al. Medication adherence and fracture risk among patients on bisphosphonate therapy in a large United States health plan. Bone 50 (2012) 870–875. Imaz I, Zegarra P, Gonzalez-Enriquez J, Rubio B, Alcazar R, Amate JM. Poor bisphosphonate adherence for treatment of osteoporosis increases fracture risk: systematic review and meta- analysis. Osteoporos Int 2010;21:1943–51. Menditto E, Citarella A, Cammarota S, de Portu S, Mantovani L G, Riegler S. Prevalence, incidence and persistence of antidepressant drug prescribing in the Italian general population: retrospective database analysis, 2005-2007. [Abstract] Value in Health 2009; 12 (7): A353. Disclosure of Interest: None Declared